1 Public Records of the Colony of Connecticut 542-43 (J. Hammond Trumbull ed., 1850) (enacted 1650) - (:unkn) unknown (My University, 1650)
Required all persons above sixteen years old to bear arms. All males will have a musket or other gun in continual readiness and fit for service.
Keywords: REQUIRED POSSESSION